Lignin valorization: Status, challenges and opportunities. (March 2022) - Sethupathy, Sivasamy; Murillo Morales, Gabriel; Gao, Lu; Wang, Hongliang; Yang, Bin; Jiang, Jianxiong; Sun, Jianzhong; Zhu, Daochen
Graphical abstract: Highlights: Estimated potential use of lignin from agricultural/forestry residues. Priority for lignin use based on key residual crops. Recent developments in applications of lignin were explained. Proposed strategies for lignin valorization and lignin-based biorefineries. Additional research is required to achieve better lignin valorization. Abstract: As an abundant aromatic biopolymer, lignin has the potential to produce various chemicals, biofuels of interest through biorefinery activities and is expected to benefit the future circular economy. However, lignin valorization is hindered by a series of constraints such as heterogeneous polymeric nature, intrinsic recalcitrance, strong smell, dark colour, challenges in lignocelluloses fractionation and the presence of high bond dissociation enthalpies in its functional groups etc. Nowadays, industrial lignin is mostly combusted for electricity production and the recycling of inorganic compounds involved in the pulping process. Given the research and development on lignin valorization in recent years, important applications such as lignin-based hydrogels, surfactants, three-dimensional printing materials, electrodes and production of fine chemicals have been systematically reviewed. Finally, this review highlights the main constraints affecting industrial lignin valorization, possible solutions and future perspectives, in the light of its abundance and its potential applications reported in the scientific literature.